Interstitial high-dose-rate brachytherapy in locally advanced and recurrent vulvar cancer - Kellas-Ślęczka, Sylwia; Białas, Brygida; Fijałkowski, Marek; Wojcieszek, Piotr; Szlag, Marta; Cholewka, Agnieszka; Ślęczka, Maciej; Kołosza, Zofia (Journal of Contemporary Brachytherapy, 2016)
Purpose : The aim of the study was to report our experience with high-dose-rate interstitial brachytherapy (HDR-ISBT) in locally advanced and recurrent vulvar cancer. Material and methods : Between 2004 and 2014, fourteen women with locally advanced or recurrent vulvar cancer were treated using HDR-ISBT in our Centre. High-dose-rate interstitial brachytherapy was performed as a separate treatment or in combination with external beam radiotherapy (EBRT) (given prior to brachytherapy). Results : Patients were divided into: group I (n = 6) with locally advanced tumors, stages III-IVA after an incisional biopsy only, and group II (n = 8) with recurrent vulvar cancer after previous radical surgery. In group I, median follow up was 12 months (range 7-18 months); 1-year overall survival (OS) was 83%. Transient arrest of cancer growth or tumor regression was noticed in all patients but 4/6 developed relapse. Median time to failure was 6.3 months (range 3-11 months). The 1-year progression-free survival (PFS) was 33%. In group II, median follow up was 28 months (range 13-90 months). The 1-year and 3-year OS was 100% and 80%, respectively. The arrest of cancer growth or tumor regression was achieved in all patients. In 4/8 patients neither clinical nor histological symptoms of relapse were observed but 4/8 women experienced relapse. Median time to failure was 31 months (range 13-76 months). The 1-year and 3-year PFS was 100% and 62.5%, respectively. Two patients (14.3%) in group II had severe late toxicity (G3). Conclusions : High-dose-rate interstitial brachytherapy is a well-tolerated treatment option in selected patients with advanced or recurrent vulvar cancer. It is a safe and effective treatment modality for advanced and recurrent vulvar cancer, yielding good local control with acceptable late treatment related side effects. In our study, patients with recurrent vulvar cancer had better results in HDR-ISBT treatment, probably because of the smaller tumor volume. This hypothesis should be verified in a larger group of patients.